Encouraging entrepreneurship and new business management: A model for creating industry leaders - Rustiadi, Sonny (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to identify and propose an entrepreneurship and new business management model relevant for cultivating future industry leaders. The research emphasizes comparative insights into regional entrepreneurial ecosystems, focusing on Bandung Raya and Tasikmalaya Raya, to highlight strengths, weaknesses, and opportunities for balanced regional development. Methodology: The study adopts a quantitative and comparative design, analyzing survey data from 76 respondents representing multiple sectors. Using descriptive statistics and ecosystem benchmarking, the research evaluates six domains of the entrepreneurial ecosystem finance, policy, culture, support, human capital, and market access to assess regional variations and strategic needsl. Results The collected data show that Bandung excels in entrepreneurial culture (84.20%), regulatory policy (81.25%), workforce (78.98%), and market access (85.23%), while Tasikmalaya Raya leads in ecosystem support (84.38%) but faces challenges in access to finance (71.25%) and markets (68.13%). Conclusions: The results confirm that entrepreneurial ecosystem disparities significantly affect business sustainability. Bandung’s mature ecosystem offers competitive advantages, while Tasikmalaya’s strong social support is insufficient to compensate for structural gaps in finance and human capital. Limitations: The study is limited to two regions in West Java, restricting generalizability. It also relies on self-reported survey data, which may introduce bias. Contribution: Therefore, enhancement strategies are required, including strengthening financial access, improving human resource quality, as well as digitalization and market expansion for entrepreneurs in Tasikmalaya Raya. With these measures, the entrepreneurial ecosystems in both regions can develop more evenly and contribute to overall regional economic growth.